Políticas públicas de gestão da força de trabalho: a precarização do trabalho do bolsista recém-formado em projetos de extensão nas universidades públicas do Estado do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The present work aims to reflect on the University extension in the State of Paraná as a space of contradictions. The analysis, delimited by the extension policy of the Universidade Sem Fronteiras (University Without Borders) Program, more specifically in the documental analysis of the public notices and selection notices for extension projects and public notices that select and compose work teams related to the proposals established by that policy, has as a centrality of the reflections the devices (“les dispositifs”) presented in the notices, observed in conjunction with the legal framework of University extension, related to the socio-legal aspects of work management in this policy and, consequently, in these projects. Socio-historical incursions about the subjects of State Reform, Administrative Reform, Precarious Work and Neoliberalism occurred with the objective of understanding the elementary characteristics that set them to then combine these elements in the analysis and contextualize the University extension. This research has as its central question the overlays between the State, Public Policies of Workforce Management and Public University Extension, and it is based on the processes of work precarization in the scope of the provision of part of public services. We observed with this research a form of precarious work that results from the combination of legal provisions in university extension and a public services management strategy that has neoliberal rationality as a background. This form of work affects a highly educated young segment, is marked by the absence of social and labor rights, workplace turnover, temporary contracts and takes the form of an extension scholarship.
Keywords: trabalho precário; extensão universitária; recém-formados; precarious work; university extension; newly graduated; CNPQ::CIENCIAS SOCIAIS APLICADAS